2016
DOI: 10.1371/journal.pgen.1005758
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Variant Regulates RNA Polymerase II Transcription Termination and Dual Strand Transcription of siRNA Loci in Trypanosoma brucei

Abstract: Base J, β-D-glucosyl-hydroxymethyluracil, is a chromatin modification of thymine in the nuclear DNA of flagellated protozoa of the order Kinetoplastida. In Trypanosoma brucei, J is enriched, along with histone H3 variant (H3.V), at sites involved in RNA Polymerase (RNAP) II termination and telomeric sites involved in regulating variant surface glycoprotein gene (VSG) transcription by RNAP I. Reduction of J in T. brucei indicated a role of J in the regulation of RNAP II termination, where the loss of J at speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
133
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(138 citation statements)
references
References 96 publications
5
133
0
Order By: Relevance
“…For example, a histone H3 variant, a bloodstream stagespecific modified DNA base known as J or hydroxymethyluracil (22,23), the chromatin remodeling ISWI complex (24), the histone H3K76 trimethyltransferase DOT1B (25), and the telomere-associated protein RAP1 (26) all facilitate VSG-ES silencing. In addition, cohesin function facilitates maintenance of the active VSG-ES (27), and inositol phosphate signaling impacts VSG-ES regulation (28).…”
mentioning
confidence: 99%
“…For example, a histone H3 variant, a bloodstream stagespecific modified DNA base known as J or hydroxymethyluracil (22,23), the chromatin remodeling ISWI complex (24), the histone H3K76 trimethyltransferase DOT1B (25), and the telomere-associated protein RAP1 (26) all facilitate VSG-ES silencing. In addition, cohesin function facilitates maintenance of the active VSG-ES (27), and inositol phosphate signaling impacts VSG-ES regulation (28).…”
mentioning
confidence: 99%
“…Finally, although it has been long thought that RNA Pol II transcriptional regulation does not operate in these organisms, recent reports have suggested that trypanosomes could regulate RNA Pol II transcription by epigenetic mechanisms (Ekanayake and Sabatini ; Reynolds et al. ; Stanne and Rudenko ). Results reported in this paper present the first experimental evidence showing that the RBP TbRRM1 plays a key role in RNA Pol II transcriptional regulation in T. brucei .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, silent ESs are marked with an unusual modified glucosylated nucleotide called Base J, which is incorporated in a gradient that increases towards the telomere end and could play some role in silencing these telomeric VSGs [34,35]. Additionally, different histone variants and modifications have also been shown to play a role in the down-regulation of ESs (Figure 2).…”
Section: How Is Vsg Expression Controlled In a Monoallelic Fashion?mentioning
confidence: 99%
“…The histone variant H3.V is enriched around the termination region of Pol II transcription units [25]. Knockdown of histone variant H3.V not only results in the disruption of Pol II transcription termination but also causes the derepression of the silent telomeric ESs [34,35]. Histone modifications also play an important role in ES control.…”
Section: How Is Vsg Expression Controlled In a Monoallelic Fashion?mentioning
confidence: 99%